Kajian Akademik Undang-Undang No. 33 Tahun 2014 Tentang Pemberlakuan Vaksin Masal - Dodi Yarli; Hikmi Wasiatul lmiyah (INSTITUT AGAMA ISLAM TAZKIA, 2019)
This study raises the theme about the issue of vaccine rejection which is rumored theexistence of pig substance in it, then with this issue correlated with LPPOM MUI authorized incertifying halal of product or Service. The purpose of this theme is to know the strength of the lawand in its application, and to know the Islamic law firom the halal aspect of the vaccine, then theresults of both will be in concert to produce laws relevant to Indonesian society and achieve thebenefit. The method used in the formulation of this study is normative legal studies and sadd azdzari'ahwhich is a form of comparative legal studies. The results of this thesis will explain theimportance of vaccines and Solutions for the government to respond to this vaccine rejection. Andthe results of this study conclusion leads to criticism and suggestions of UUJPH and suggestionsfor governments and vaccine producers.